Diabetes mellitus and odontogenic infections: a life threatening combination in Ludwig’s angina - Kumari, Anjana; Maan, Arvinder Singh; Singh, Satinderpal; Saran , Simerpreet Kaur (International Journal of Research in Medical Sciences, 2024)
Background: The present study was a prospective study which was aimed to assess the risk factors, microbiological profile, management strategies of Ludwig’s angina patients and its association with odontogenic infections and diabetes mellitus. Methods: The study population consisted of 40 patients of Ludwig’s angina those presented to and were managed in the department of ENT, Government Medical College, Amritsar, Punjab, India, from January 2022 to May 2023. All the patients exhibiting clinical symptoms and signs of Ludwig’s angina were examined and a detailed history of the duration of each symptom, present and past illness, dental infection, throat infection, diabetes mellitus was taken. Results: It was observed that in 85% cases of Ludwig’s angina history of dental infection was present. History of diabetes mellitus was present in 50% cases followed by tooth extraction (10%). Streptococcus viridans was found in 22.5% patients, Staphylococcus aureus (12.5%) and no growth was seen in 52.5% cases. Major co-morbidity was diabetes mellitus (50%), followed by HIV and HCV infections in 15% patients. Surgical drainage was performed in 90% cases including tracheostomy in 12.5% cases rest 10% patients were treated medically. Conclusions: Uncontrolled diabetes mellitus, delayed treatment of odontogenic infection complicates the management of Ludwig’s angina and leads to life threatening complications. Ludwig’s angina should be actively treated as a surgical and medical emergency in which incision and drainage is required as early as possible. Tracheostomy should be considered as an emergency measure to relieve the respiratory obstruction.